x^2(x-2)>0
=>x^2 và x-2 cùng dấu
mà x^2 > 0 với mọi x
=>x-2>0
=>x>2
vậy với x>2 thì x^2(x-2)>0
Đúng 0
Bình luận (0)
x^2(x-2)>0
=>x^2 và x-2 cùng dấu
mà x^2 > 0 với mọi x
=>x-2>0
=>x>2
vậy với x>2 thì x^2(x-2)>0
Tim x, y thuoc Z biet : | x-2| + (x-y+1)^2 =0
tim x thuoc Z biet :
(x-1)^2 =(x-3)^4
HELP ME:0!!
tim x thuoc z,biet
(x-5)^2=0
Tim X thuoc Z biet :
(x-3).(x+2)<0
Tim x biet
(x-2)(x+3)<0 voi x thuoc z
tim x,y thuoc z biet (x-2).(y+12)<0
tim x thuoc Z biet (22-9)x(x2-37)<0
tim x,y,z thuoc Z biet /2x-4/+/y+2/+/2x+3y-z/=0
tim x thuoc z biet
(x-1)(x-3)=-5
(x+1)(x+4)=0
(x^2-4)(x^2-19)<0